Statin-Associated Necrotizing Autoimmune Myositis Complicated by an Uncommon Adverse Effect to Treatment. (25th June 2019) - Fung, Brian M.; Heinze, Emil R.; Wong, Andrew L.
Abstract : Statin-associated necrotizing autoimmune myositis (NAM) is an autoimmune condition characterized by severe acute-onset proximal muscle weakness, a very high creatinine kinase (CK) level, and prominent myofiber necrosis and minimal lymphocytic infiltration on muscle biopsy. Unlike self-limited statin myopathy, this condition usually requires aggressive immunomodulation therapy to assist recovery and prevent future disability. In this case report, we present a patient who developed progressive muscle weakness after taking atorvastatin for one year. At initial presentation, her CK level was 28, 000 U/L. She was diagnosed with statin-associated NAM and started on high-dose intravenous solumedrol, mycophenolate, and intravenous immunoglobulin (IVIG) therapy. However, she subsequently developed acute bilateral vision loss and right side hemineglect; she was diagnosed with posterior reversible encephalopathy syndrome (PRES), thought to be a possible delayed adverse reaction to IVIG. IVIG was discontinued, and the patient was treated with supportive therapy. At six-month follow-up, she had significant improvement in muscle strength and vision.